Interprofessional education and collaborative practice curriculum development – a proposed validation process. - Pitout, Hanlie; Barnard-Ashton, Paula; Adams, Fasloen; du Toit, Sanetta (Journal of Interprofessional Care)
Validating an interprofessional education and collaborative practice (IPECP) curriculum prior to implementation is uncommon. A sound empirical investigation involving external and internal participants considered four criteria: relevance, consistency, practicality, and effectiveness, as part of an educational design research process to assess whether the proposed curriculum content was valid for the South African healthcare higher education context. Participants provided quantitative input on the four criteria on a visual analog scale (0–100) and qualitative comments to suggest improvements to the proposed curriculum. Descriptive statistics and deductive thematic analysis were used for data analysis. The participants lauded the proposed curriculum. Relevance generated strong agreement and consensus (m = 99, IQR = 6.75), with a lower, but still adequate, rating and consensus for practicality (m = 85.5, IQR = 25.75). The consistency and effectiveness, rated across years of study and streams, indicated in ratings and consensus with an increase across years of study from the first to the last year. Of the streams, the proposed Research and Ethics stream appeared to be the most problematic with moderate consensus (m = 90, IQR = 19.75). Curriculum validation before implementation illuminated concerns requiring refinement and strengthening responsive strategies to ensure a tailored implementation of the proposed curriculum.